Practical application of altitude/hypoxic training for Olympic medal performance: The Team USA experience - Wilber, R. L. (Journal of Science in Sport and Exercise, 2022)
Although scientifc conclusions remain equivocal, there is evidence-based research, as well as anecdotal support, suggesting that altitude training can enhance performance among Olympic level athletes, particularly in endurance sport. This appears to be due primarily to hypoxia-induced increases in total hemoglobin mass and subsequent improvements in maximal oxygen uptake and other factors contributing to aerobic performance. Although less clear, it is possible that non-hematological adap tations may contribute secondarily to improvements in post-altitude performance. These physiological efects are most likely realized when the altitude exposure is of sufcient "hypoxic dose" to provide the necessary stimuli for performance-afecting changes to occur via hypoxia-inducible factor 1a (HIF-1a) and hypoxia-inducible factor 2a (HIF-2a) pathways and their downstream molecular signaling. Team USA has made a strong commitment over the past 20 years to utilizing altitude training for the enhancement of performance in elite athletes in preparation for the Olympic Games and World Championships. Team USA`s strongest medal-producing Olympic sports—USA Swimming and USA Track and Field—embraced altitude training several years ago, and they continue to be leaders within Team USA in the practical and successful application of altitude training. Whereas USA Swimming utilizes traditional "live high and train high" (LH+TH) altitude training, USA Track and Field tends more toward the use of the altitude training strategy whereby athletes live high (and potentially sleep higher, either naturally or via simulated altitude), while training high during moderate-intensity (<lactate threshold 2) training sessions, and train low during high-intensity (>lactate threshold 2) training sessions (LH+ TH[<LT]+ TL[>LT]). Although USA Swim ming and USA Track and Field have taken diferent approaches to altitude training, they have been equally successful at the Olympic Games and World Championships, both teams being ranked frst in the world based on medals earned in these major international competitions. In addition to USA Swimming and USA Track and Field, several other Team USA sports have had consistently competitive performance results in conjunction with regular and systematic altitude training blocks. The purpose of this paper was to describe select altitude training strategies used by Team USA athletes, and the impact of those strategies on podium performance at major international competitions, specifcally the Olympic Games and World Championships.